Long-term risk of sudden cardiac death in hypertrophic cardiomyopathy: a cardiac magnetic resonance outcome study. (17th January 2021) - Greulich, Simon; Seitz, Andreas; Herter, Diana; Günther, Fabian; Probst, Sabine; Bekeredjian, Raffi; Gawaz, Meinrad; Sechtem, Udo; Mahrholdt, Heiko
Abstract: Aims: Sudden cardiac death (SCD) is an appalling complication of hypertrophic cardiomyopathy (HCM). There is an ongoing discussion about the optimal SCD risk stratification strategy since established SCD risk models have suboptimal discriminative power. The aim of this study was to evaluate the prognostic value of late gadolinium enhancement (LGE) cardiac magnetic resonance (CMR) for SCD risk stratification compared to the European Society of Cardiology (ESC) SCD risk score and traditional risk factors in an >10-year follow-up. Methods and results: Two hundred and twenty consecutive patients with HCM and LGE-CMR were enrolled. Follow-up data were available in 203 patients (median age 58 years, 61% male) after a median follow-up period of 10.4 years. LGE was present in 70% of patients with a median LGE amount of 1.6%, the median ESC 5-year SCD risk score was 1.84. In the overall cohort, SCD rates were 2.3% at 5 years, 4.8% at 10 years, and 15.7% at 15 years, independent from established risk models. An LGE amount of >5% left ventricular (LV) mass portends the highest risk for SCD with SCD prevalences of 5.5% at 5 years, 13.0% at 10 years, and 33.3% at 15 years. Conversely, patients with no or ≤5% LGE of LV mass have favourable prognosis. Conclusions: LGE-CMR in HCM patients allows effective 10-year SCD risk stratification beyond established risk factors. LGE amount might be added to established risk models to improve its discriminatory power. Specifically, patients with >5% LGE should be carefully monitored and might be adequate candidates for primary prevention implantable cardioverter-defibrillator during the clinical long-term course. Graphical Abstract: